Consensus on Screening, Diagnosis, and Staging Tools for Prostate Cancer in Developing Countries: A Report From the First Prostate Cancer Consensus Conference for Developing Countries (PCCCDC). (2021) - Carneiro, Arie; Racy, Douglas; Bacchi, Carlos Eduardo; Leite, Katia Ramos Moreira; Filippi, Renee Zon; Martins, Igor Austin Fernandes; Salvajoli, Joao Victor; Hanriot, Rodrigo de Morais; Baroni, Ronaldo Hueb; Sarkis, Alvaro Sadek; Pompeo, Antonio Carlos Lima; Benigno, Bruno Santos; et al.
Abstract : PURPOSE: To generate and present the survey results on critical issues relevant to screening, diagnosis, and staging tools for prostate cancer (PCa) focused on developing countries. METHODS: A total of 36 of 300 questions concern the main areas of interest of this paper: (1) screening, (2) diagnosis, and (3) staging for various risk levels of PCa in developing countries. A panel of 99 international multidisciplinary cancer experts voted on these questions to create recommendations for screening, diagnosing, and staging tools for PCa in areas of limited resources discussed in this manuscript. RESULTS: The panel voted publicly but anonymously on the predefined questions. Each question was deemed consensus if 75% or more of the full panel had selected a particular answer. These answers are based on panelist opinion not a literature review or meta-analysis. For questions that refer to an area of limited resources, the recommendations consider cost-effectiveness and the possible therapies with easier and greater access. Each question had five to seven relevant answers including two nonanswers. The results were tabulated in real time. CONCLUSION: The voting results and recommendations presented in this document can be used by physicians to support the screening, diagnosis, and staging of PCa in areas of limited resources. Individual clinical decision making should be supported by available data; however, as guidelines for screening, diagnosis, and staging of PCa in developing countries have not been developed, this document will serve as a point of reference when confronted with this disease.